EPIDEMIC ANALYSIS, MATHEMATICAL MODELLING AND NUMERICAL SIMULATION OF COVID-19 TRANSMISSION - Triyana, Eka; Widowati, Widowati (Journal of Fundamental Mathematics and Applications (JFMA), 2025)
This research develops a model with seven compartments SEIQDHR for the spread of COVID-19, with detected and treated individual behavior changes affecting disease transmission. The Next Generation Matrix is used to analyze local and global stability and to calculate the basic reproduction number. Then, the analysis of disease-free equilibrium and endemic equilibrium. Stability analysis shows that the equilibrium point is locally asymptotically stable when the basic reproduction number is less than one and globally asymptotically stable when it is greater than one. The results of the sensitivity analysis show that the transmission rate, the progression rate from exposure, and the detection rate are parameters that significantly influence the dynamics of disease spread. Numerical simulations were used to validate the analysis results and identify key parameters that contribute most to the spread of the disease among affected, infected, quarantined, diagnosed, and hospitalized individuals.